“We Were the Teachers, not the Observers”: Transforming Teacher Preparation through Placements in a Creative, After-School Program - Nikki Holland; Iris Shepard; Christian Z. Goering (Journal of the Assembly for Expanded Perspectives on Learning, 2011)
Teacher preparation at one university shifts pre-service observation to hands-on integration of the arts in an after-school program called Razorback Writers.